Automated assembly scaffolding using RagTag elevates a new tomato system for high-throughput genome editing - Alonge, Michael; Lebeigle, Ludivine; Kirsche, Melanie; Jenike, Katie; Ou, Shujun; Aganezov, Sergey; Wang, Xingang; Lippman, Zachary B.; Schatz, Michael C.; Soyk, Sebastian (Genome Biology, 2022)
Advancing crop genomics requires efficient genetic systems enabled by high-quality personalized genome assemblies. Here, we introduce RagTag, a toolset for automating assembly scaffolding and patching, and we establish chromosome-scale reference genomes for the widely used tomato genotype M82 along with Sweet-100, a new rapid-cycling genotype that we developed to accelerate functional genomics and genome editing in tomato. This work outlines strategies to rapidly expand genetic systems and genomic resources in other plant species.